Intercropping French Bean with Brinjal at Varying Planting System (Bangladesh Agronomy Journal, 2019)
The experiment was carried out at the research field of Agricultural Research Station, Rajbari, Dinajpur during rabi season of 2014-15 and 2015-16 to find out suitable crop combination for higher productivity and economic return. Six different treatments viz. T1 = Sole brinjal (75 cm x 60 cm), T2 = Sole french bean (30 cm x 10 cm), T3 = Brinjal normal row (100%) + 1 line french bean between brinjal (33%), T4 = Brinjal normal row (100%) + 2 lines french bean between brinjal (66%), T5 = Brinjal paired row (100%) + 3 lines french bean between brinjal (40%) and T6 = Brinjal paired row (100%) + 4 lines french bean between brinjal (53%) were evaluated. The results revealed that the highest mean fruit yield of brinjal (44.26 t ha-1) and french bean (20.96 t ha-1) was obtained in sole cropping of component crops. Under intercropping, the highest brinjal yield (38.61 t ha-1) was recorded in brinjal normal row + 1 line french bean between brinjal, while, the highest french bean yield (16.06 t ha-1)  in brinjal normal row + 2 lines french bean between brinjal. The highest mean brinjal equivalent yield (58.72 t ha-1) and land equivalent ratio (1.50) was also obtained in brinjal normal row + 2 lines french bean between brinjal. The highest gross return (Tk. 4,69,760 ha-1), gross margin (Tk. 3,66,440 ha-1), and BCR (4.54) were obtained in brinjal normal row + 2 lines french bean between brinjal and the lowest in sole french bean. The overall results indicated that among the intercrop combinations brinjal normal row + 2 lines french bean between brinjal was found suitable for total productivity and economic return of the system.Bangladesh Agron. J. 2018, 21(2): 1-6